Development of the Adomian's Method for Solving non-linear Fredholm-Fredholm Integral Equations - Junaid Mustafa (College of Education for Pure Sciences, 1999)
Abstract: A new and effective direct method to determine the numerical solution of non- linear Fredholm-Fredholm integral equations is proposed. The method is based on a series solution for the unknown quantity by Adomian's method. We obtained very good results compared with classic Adomian's method Some numerical examples are provided to illustrate accuracy and computational efficiency of the method.